The house on Prytania - White, Karen (Karen S.) (White, Karen (Karen S.). Royal Street novel, 2023)
"Nola Trenholm may not be psychic herself, but she's spent enough time around people who are to know when ghosts are present, and there are definitely a few lingering spirits in her recently purchased Creole cottage in New Orleans. Something, or someone, is keeping them tethered to this world. And not all of them are benign. But with the sudden return of Sunny Ryan, Beau Ryan's long-lost sister, Nola has plenty to distract her from her ghostly housemates. Especially when the tempting--yet firmly unavailable--Beau, wanting to mete out justice to those he blames for Sunny's kidnapping, asks Nola for a favor that threatens to derail her hard-won recovery and send her hurtling backward. He asks her to welcome Michael Hebert back into her life, even though Michael is the reason for Nola's bruised heart. Beau is convinced that Michael's powerful family was behind Sunny's disappearance and that Michael is the key to getting information the police won't be able to ignore--if Nola is willing to risk everything for which she's worked so hard. Torn between helping Beau and protecting herself, Nola doesn't realize until it's almost too late why the ghosts are haunting her house--a startling revelation that will throw her and Beau together to fight a common enemy. Assuming Nola can get Beau to listen to what the spirits are trying to tell him, because ignoring them could prove to be a fatal mistake..."--